Case StudyEstimating diesel fuel exposure for a plumber repairing an underground pipe. Issue 4 (3rd April 2017) - Finn, Mary; Stenzel, Mark; Ramachandran, Gurumurthy
ABSTRACT: We estimated the diesel fuel exposure of a plumber repairing an underground water line leak at a truck stop. The repair work was performed over three days during which the plumber spent most of his time in a pit filled with a mixture of water and diesel fuel. Thus, the plumber was exposed via both the inhalation and dermal routes. While previously asymptomatic, he was diagnosed with acute renal failure 35 days after working at this site. No measurements were available for estimating either inhalation or dermal exposures or the cumulative dose and, therefore, two different approaches were used that were based on simple models of the exposure scenario. The first approach used the ideal gas law with the vapor pressure of the diesel fuel mixture to estimate a saturation vapor concentration, while the second one used a mass balance of the petroleum hydrocarbon component of diesel fuel in conjunction with the Henry's Law constant for this mixture. These inhalation exposure estimates were then adjusted to account for the limited ventilation in a confined space. The inhalation exposure concentrations predicted when handling the water layer alone is much lower than that expected from the organic layer. This case study illustrates the large differences in inhalation exposure associated with volatile organic layers and aqueous solution containing these chemicals. The estimate of dermal exposure was negligible compared to the inhalation exposure because the skin presents a much smaller surface area of exposure to the contaminant compared to the lungs. The methodology presented here is useful for situations where little information is available for more formal mathematical exposure modeling, but where adjustments to the worst-case exposures, estimated simply, can provide reasonable exposure estimates.